Perbaikan Sifat Biologi Tanah Perkebunan Karet (Havea brasiliensis) Dengan Menggunakan Teknik Biopori - Rina Maharany (Agrium, 2019)
The estimation of the International Rubber Study Group (IRSG) is estimated to be a lack of rubber supply in the period of the next two decades. For this reason, the government has set the target of developing Indonesian rubber production at 3-4 million tons/year by 2025. The production target can only be achieved if at least 85% of the currently less productive rubber plantation area is successfully rejuvenated with various technologies to improve soil productivity and using superior rubber clones.Biopori hole is a vertical hole into the ground to increase the rate of infiltration of rainwater. This research was done in rubber land Jaharun B of village, sub district of Galang, Deli Serdang district, on Februari until Agustus 2017. This research was used Randomized Blok Design Non Factorial with 4 dose of rubber litter treatment is K1 : Control, K2 : 3 kg, K3 : 3.5 kg, K4 : 4 kg.      The addition of rubber litter treatment by biopori was able to repair the biology characteristic of soil for all parameters {(C-organic (%), N-total (%), C/N and amount of soil microbial)}with the addition of rubber litter is 3.5 kg. The more given of rubber litter into the ground, it can to repair the chemical characteristic of soil in rubber plantation.  Keyword : Biopori, Biology Charateristic of Soil, Productivity in Rubber Plantation